SPELLING ERROR ANALYSIS IN STUDENTS’ WRITING ENGLISH COMPOSITION - Tira Nur Fitria (Getsempena English Education Journal, 2020)
This research has objective to find out the kind of spelling errors written by the students and to determine the most dominant kind of spelling error written by the students of STIE AAS Surakarta in the academic year 2017/2018. This study used a descriptive qualitative approach. In this study, researchers revealed conclusions by collecting data. The object of the research were taken from 24 students of STIE AAS Surakarta, especially in the 2017/2018 academic year. In collecting data, the researcher used the documentation method. In analyzing errors, the steps were the identification of errors, classification of errors, description of errors, explaining errors, and tabulation of data. The data were tabulated to determine the frequency of errors found in the students’ writing composition. From the results of the study, it was found that there are some errors found in the results of student essays in the aspect of spelling as 50 data which consist of some errors such as in omission as 20 data or 40 %, in substitution as 14 data or 28 %, in insertion/addition as 10 data or 20 % and transposition as 6 data or 12 %. While the most dominant spelling error occurs in the aspect of omission as 20 data or 40 %.